Green Synthesis of Barium Doped Titanium Dioxide Using Palm Leaf Extract (Elaeis guineensis Jacq.) - Andriayani Andriayani; Henny Dumarta Hutapea; Muhammad Taufik (Journal of Chemical Natural Resources, 2025)
Conventional synthesis of titanium dioxide (TiO₂) nanoparticles often involves the use of toxic chemicals, high costs, and extreme operating conditions. This research aims to develop a cost-effective and environmentally friendly green synthesis method for TiO₂ by utilizing oil palm leaf (Elaeis guineensis Jacq.) extract as a reducing and stabilizing agent. Subsequently, doping with barium (Ba) was carried out to enhance the photocatalytic, optical, and electrical properties of the resulting TiO₂. Phytochemical analysis revealed that oil palm leaf extract contains alkaloids, flavonoids, terpenoids, saponins, and tannins, which play a role in the reduction and stabilization processes of TiO₂ nanoparticles. Characterization using Fourier Transform Infrared Spectroscopy (FTIR) identified Ti-O bonds in pure TiO₂ at a wavenumber of 588 cm⁻¹, and a shift in absorption peaks in the range of 548-595 cm⁻¹ in Ba-doped TiO₂ indicated the formation of the barium titanate phase. X-ray Diffraction (XRD) analysis showed that Ba doping increased the crystallite size of TiO₂ from 1.17 nm to 1.65 nm, which may have implications for photocatalytic applications.